Assessing Shared Decision-Making in Cystic Fibrosis Care Using collaboRATE: A Cross-Sectional Study of 159 Programs. (18th August 2021) - Homa, Karen; Stevens, Gabrielle; Forcino, Rachel; Scalia, Peter; Mertz, Pamela; Elwyn, Glyn
There are numerous opportunities for shared decision-making (SDM) in cystic fibrosis (CF) care, yet little is known about patients' SDM experiences. This study evaluated SDM across 159 CF care programs (4024 participants) in the United States. Shared decision-making was assessed using the patient-reportedcollabo RATE measure, which was included in the CF Foundation's Patient and Family Experience of Care Survey over 18 months. Overall, 69% of respondents reported experiencing SDM. Respondents at pediatric programs were more likely to experience SDM than those at adult programs (72% vs 67%, P < .001). Multivariable logistic regression analyses showed a relationship between SDM and patient age, whereby SDM was less likely to occur with patients aged 18 to 24 years, compared to some younger and older age groups ( P = .02-<.001). Shared decision-making was more likely to occur at pediatric programs when patients had better general health ( P = .02-<.01), and at pediatric and adult programs when patients had better mental health ( P = .02-<.001). Disparities in SDM experiences highlight a need to improve decision-making processes in CF care. Interventions tailored for improving SDM among specific patient populations may be particularly advantageous.